Substitute Yeast Extract While Maintaining Performance: Showcase Amorpha‐4,11‐Diene Production - Carlos Castillo‐Saldarriaga; Christine N. S. Santos; Stephen Sarria; Parayil K. Ajikumar; Ralf Takors (Microbial Biotechnology)
ABSTRACT Yeast extract (YE) is a complex nutritional source associated with high performance on microbial production processes. However, its inherent compositional variability challenges its scalability. While prior efforts have focused on growth‐associated products, the dynamics of growth‐uncoupled production, which leads to higher production rates and conversion yields, still need to be explored. This production scenario is common in large‐scale applications. This study presents a systematic approach to replace YE for the production of the terpene amorpha‐4,11‐diene in Escherichia coli. Sequential processing was successfully applied to identify glutamic acid, alanine, leucine, valine, isoleucine and glycine as the key amino acids (AAs) under slow‐growth conditions. Thoroughly applying biomass retention as part of sequential processing increased production capacity by 45% using these AAs instead of YE. Further studies, including flux balance analyses, targeted pyruvate as the common AA precursor. The optimized fed‐batch process feeding pyruvate with 0.09 gPyr h−1 enhanced amorpha‐4,11‐diene production by 37%, although adding only 1% carbon via pyruvate. Flux balance analysis revealed the criteria for optimum pyruvate feeding, for example, to prevent succinate secretion and maintain the NADH/NAD+ balance. These findings illustrate the interplay between media composition and metabolic activity and provide a successful guideline for identifying lean, best‐performing media for industrial applications.